Land use, land cover change intensity, and landscape fragmentation in the Western Nghe An Biosphere Reserve from 1990 to 2020 - Tran Van, Truong; Dang Thi, Ngoc; Nguyen Huu, Duy; Pham Van, Manh; Ngo Van, Liem; Pham Viet, Thanh; Nguyen Anh, Duc; Nguyen Van, Hong (Vietnam Journal of Earth Sciences, 2025)
Land-use and land-cover (LULC) change, as well as landscape fragmentation, significantly impact biodiversity conservation in biosphere reserves. This paper aims to analyze LULC change intensity and landscape fragmentation, and to test their relationship within the Western Nghe An Biosphere Reserve (WNABR) from 1990 to 2020. LULC data from 1990, 2000, 2010, and 2020, covering 13 LULC types, were analyzed for LULC change, LULC change intensity at the interval and categorical levels, and landscape fragmentation using landscape metrics at class and landscape levels. Pearson’s correlation coefficient was then employed to examine the relationship between land change intensity and landscape fragmentation. The results indicate that from 1990 to 2020, high-developed areas, low-developed areas, and bamboo areas consistently increased, while plantation land, scrub/shrub, grassland/herbaceous vegetation, other croplands, and rice paddies declined. Evergreen broadleaf forest areas remained stable and dominant. Land change intensity was above average from 1990 to 2000, then gradually decreased from 2000 to 2020. Evergreen broadleaf forests, open water, other croplands, and rice paddies exhibited lower land change intensity than other types. There is a general trend of decreasing fragmentation within the WNABR. Evergreen broadleaf forest and plantation land are composed of large, less fragmented patches, while the remaining LULC types are typically fragmented into small, scattered patches. LULC change intensity and landscape fragmentation increased from the core zone to the buffer and transition zones. There is a significant positive linear relationship between LULC change intensity and the number of patches (NP).